Pengaruh Tata Kelola Perusahaan Terhadap Struktur Modal di Indonesia - Perwitasari, Indah; Yusfania, Bilkis; Lestari, Henny Setyo (SEIKO : Journal of Management & Business, 2024)
This study aims to evaluate the impact of corporate governance on the capital structure of manufacturing companies on the IDX for the 2019-2023 period. The independent variables included board size, board independence, and frequency of board meetings, while the dependent variable is the debt ratio measured by the company's total debt. Using panel data regression method and purposive sampling on 55 companies, the study found that board meeting frequency has a significant negative impact on debt ratio, while board size and independence have no significant impact. The managerial implication of this result is that it is important for companies in planning capital structure and providing direction to investors regarding the risk and debt policy of the company. Kata Kunci: Capital Structure, Debt Ratio, Corporate Governance, Board Size, Board Independence, Board Independence.